Specific treatment modalities for elderly patients with chronic lymphocytic leukemia. (June 2012) - Michallet, Anne-Sophie; Feugier, Pierre; Delmer, Alain; Ysebaert, Loic; Cazin, Bruno; Dartigeas, Caroline; Fornecker, Luc; Van de Neste, Eric; Cymbalista, Florence; Lévy, Vincent; Leblond, Veronique; Troussard, Xavier
To date, the majority of trials on chronic lymphocytic leukemia (CLL) have focused on patients considerably younger than the median age of onset for CLL. As a result, no definitive treatment exists for elderly patients, especially less medically fit patients. Even today, most physicians consider chlorambucil to be an appropriate option for elderly CLL patients. Practices, however, have subsequently changed following the results of several Phase III trials. Given the potential of these new immunotherapy regimens, selecting the right treatment for elderly CLL patients is still challenging.